Design of an Application-Based Sales Information System for Koperasi XYZ - Widanengsih, Euis; Yusuf, Yusuf (Sean Institute, 2025)
This study examines the development of an application-based sales information system for Koperasi XYZ to enhance operational efficiency, financial transparency, and decision-making. The cooperative's manual system presents challenges such as data loss, recording errors, and delays in financial reporting. The research employs a qualitative and quantitative approach, utilizing observation, interviews, and document analysis to identify system requirements. The system is developed using the waterfall model, covering requirements analysis, system design, implementation, testing, and maintenance. Key technologies include Java programming and MySQL database, ensuring stability and usability. Black-box testing is applied to validate system functionality, focusing on transaction accuracy, role-based access, and financial reporting efficiency. The findings indicate that the new system significantly improves transaction speed, data accuracy, and managerial decision-making. This digital transformation strengthens Koperasi XYZ’s competitiveness, enabling better financial control, inventory management, and service quality, ensuring sustainable growth in the digital era.